2009
DOI: 10.21608/jfds.2009.112144
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Orange Juice, Peel and It’s Essential Oil on the Shelf Life of Cake

Abstract: The objective of this work was to study the effect of orange juice, peel and it's essential oil as antimicrobial agent, on the shelf life of cake when stored at room temperature and at 4 o C for 4 weeks. Sensory evaluation of different cup cake types produced from wheat flour containing different levels of orange peel and essential oil showed that there are non significant differences in taste and flavour between treatments (control with orange), orange peels 2.5% + orange juice, orange essential oil 0.3% + or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The influence of essential oils added for antimicrobial and/or preservative purposes on foods’ organoleptic physiognomy is not easily predictable, but obviously needs to be addressed case by case. For example, a previous report by Ahmed et al indicated that the addition of 0.3% of orange peel essential oil did not affect the sensory evaluation of the cupcake (Ahmed et al, 2009) [ 52 ], while in another study by Ibrahium et al, the sensory evaluation revealed that the sample containing 800 ppm of clove essential oil showed the lowest acceptability score in cakes, in addition to preservation effects (Ibrahium et al, 2013) [ 53 ]. Our results indicate that OB-EO supplementation at 0.1–0.2% did not alter the overall acceptability of the chicken nuggets, while increasing the level of supplementation to ࣙ0.3% resulted in undesirable changes in taste, flavor and mouthfeel responses of the chicken nuggets.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of essential oils added for antimicrobial and/or preservative purposes on foods’ organoleptic physiognomy is not easily predictable, but obviously needs to be addressed case by case. For example, a previous report by Ahmed et al indicated that the addition of 0.3% of orange peel essential oil did not affect the sensory evaluation of the cupcake (Ahmed et al, 2009) [ 52 ], while in another study by Ibrahium et al, the sensory evaluation revealed that the sample containing 800 ppm of clove essential oil showed the lowest acceptability score in cakes, in addition to preservation effects (Ibrahium et al, 2013) [ 53 ]. Our results indicate that OB-EO supplementation at 0.1–0.2% did not alter the overall acceptability of the chicken nuggets, while increasing the level of supplementation to ࣙ0.3% resulted in undesirable changes in taste, flavor and mouthfeel responses of the chicken nuggets.…”
Section: Discussionmentioning
confidence: 99%